Evaluation of the efficacy of MMX mesalazine therapy for moderate ulcerative colitis - O. V. Knyazev; A. V. Kagramanova; A. A. Lishchinskaya (Медицинский совет, 2021)
Introduction. Treatment of patients with ulcerative colitis (UC) requires continuous anti-relapse therapy. Mesalazines are the firstline disease-modifying drugs for the treatment of mild to moderate UC to manage exacerbations and to induce and maintain remission.This paper is aimed at comparing the efficacy of treatment of patients with pancolitis and left-sided ulcerative colitis of moderate severity, who received MMX mesalazine as monotherapy and MMX mesalazine combined with mesalazines in the form of microclysters and suppositories.Materials and methods. A comparative clinical evaluation of the outcomes of treatment of patients with moderate UC who received MMX mesalazine as monotherapy (group 1) and MMX mesalazine combined with topical mesalazine (microclysters, suppositories) (group 2) was carried out. 40 patients with UC (group 1) and 46 (group 2) were examined.Results and discussion. Two weeks after MMX mesalazine therapy initiation, 92.8% of patients in group 1 responded to MMX mesalazine therapy and continued using the drugs as monotherapy (without microclysters and suppositories). In group 1, 95.6% of patients responded to MMX mesalazine therapy and continued treatment with topical mesalazines (microclysters and suppositories). At week 12, 54.3% of 35 patients in group 1, who responded to MMX mesalazine therapy, achieved clinical remission, 45.7% achieved clinical endoscopic remission. The Mayo Score decreased from 8.0 ± 0.17 to 2.3 ± 0.3 points. At week 12, 57.1% of patients with UC in group 2, who responded to MMX mesalazine therapy, achieved clinical remission, and 42.9% achieved clinical and endoscopic remission. The Mayo Score decreased from 7.85 ± 0.14 to 2.4 ± 0.3 points. There was no statistically significant difference in the level of laboratory findings between the groups of patients at 12 weeks and at 52 weeks (p> 0.05).Conclusion. The long-term continuous administration of MMX mesalazine in patients with pancolitis and left-sided ulcerative colitis of moderate severity as monotherapy during the year is comparable in its efficacy with combined MMX mesalazine therapy and topical forms of mesalazine.